Review: Occult hepatitis C virus infection: Still remains a controversy. Issue 9 (4th June 2014) - Dzekova Vidimliski, Pavlina; Nikolov, Igor; Matevska Geshkovska, Nadica; Dimovski, Aleksandar; Rostaing, Lionel; Sikole, Aleksandar
Abstract Occult hepatitis C virus (HCV) infection is characterized by the presence of HCV RNA in the liver cells or peripheral blood mononuclear cells of the patients whose serum samples test negative for HCV RNA, with or without presence of HCV antibodies. The present study reviews the existing literature on the persistence of occult hepatitis C virus infection, with description of the clinical characteristics and methods for identification of occult hepatitis C. Occult hepatitis C virus infection was detected in patients with abnormal results of liver function tests of unknown origin, with HCV antibodies and HCV RNA negativity in serum, and also in patients with spontaneous or treatment‐induced recovery from hepatitis C. The viral replication in the liver cells and/or peripheral blood mononuclear cells was present in all clinical presentations of occult hepatitis C. The peripheral blood mononuclear cells represent an extra‐hepatic site of HCV replication. The reason why HCV RNA was not detectable in the serum of patients with occult hepatitis C, could be the low number of circulating viral particles not detectable by the diagnostic tests with low sensitivity. It is uncertain whether occult hepatitis C is a different clinical entity or just a form of chronic hepatitis C virus infection. Data accumulated over the last decade demonstrated that an effective approach to the diagnosis of HCV infection would be the implementation of more sensitive HCV RNA diagnostic assays, and also, examination of the presence of viral particles in the cells of the immune system. J. Med. Virol. 86:1491–1498, 2014. © 2014 Wiley Periodicals, Inc.